FUZZY BASED RESOURCE MANAGEMENT APPROACH FOR THE SELECTION OF BIOMASS MATERIAL (International Journal of Food and Nutritional Sciences, 2022)
Biomass is a renewable and sustainable composite biomaterial. It is made up of lignin, cellulose and hemicellulose with considerable amount of water, extractives and inorganic chemical compounds.The use of biomaterials and other biogenic wastes for energy recovery represent an eco-friendly way to use these natural fillers.Biomaterial selection is one of the most significantaspects for any conversion process, and it is a common outsourcing problem that includes material preparation, reactor performance, economic assessment and the calorific value of the products. Fuzzy systems can be quite useful in high-performance computing during the selection of biomaterials. In each engineering process, material selection is a crucial step since each material are having its own set of characteristics. This study presents the application of type-1 fuzzy set for the section of suitable biomaterial for yielding maximum bi-oil. This study focuses on seven locally available materials such as rice straw (M-1), sunflower shell (M-2), hard wood (M-3), wheat straw (M-4), sugarcane bagasse (M-5), corn cop (M-6) and palm shell (M-7). The study evaluated seven important properties of the materials such as lignin (P-1), cellulose (P-2), hemicellulose (P-3), volatile matter (P-4), fixed carbon (P-5), moisture content (P-6) and ash content (P-7). The findings demonstrated that sugarcane bagasse (M-5) is the best option for maximum bio-oil yield.